The Construction of Sustainable Palm Oil Image In Naga Naga Naga Film - Mochamad Husni; Frengki Napitupulu (Universitas Prof. Dr. Moestopo (Beragama), 2023)
The focal subject of examination is a film that portrays the establishment of palm oil plantations, while the use of Berger-Luckmann's social construction theory serves as two key factors that emphasize the importance of this research. The film